2009
DOI: 10.1073/pnas.0808722106
|View full text |Cite
|
Sign up to set email alerts
|

The protein disulfide isomerase AGR2 is essential for production of intestinal mucus

Abstract: Protein disulfide isomerases (PDIs) aid protein folding and assembly by catalyzing formation and shuffling of cysteine disulfide bonds in the endoplasmic reticulum (ER). Many members of the PDI family are expressed in mammals, but the roles of specific PDIs in vivo are poorly understood. A recent homology-based search for additional PDI family members identified anterior gradient homolog 2 (AGR2), a protein originally presumed to be secreted by intestinal epithelial cells. Here, we show that AGR2 is present wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
374
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(405 citation statements)
references
References 41 publications
20
374
4
1
Order By: Relevance
“…Beside its role in the intestine, Agr2 is also expressed in mucus-producing goblet cells and localizes with Muc5AC during airway GCM in a mouse model of experimental allergic asthma. Thus, Agr2 deficient mice display impaired export of mucins from the ER and no activation of UPR [61][62][63]. These studies support the role of Agr2 in reducing ER stress during the production of large amounts of mucins.…”
Section: Journal Of Clinical and Cellular Immunologysupporting
confidence: 63%
See 2 more Smart Citations
“…Beside its role in the intestine, Agr2 is also expressed in mucus-producing goblet cells and localizes with Muc5AC during airway GCM in a mouse model of experimental allergic asthma. Thus, Agr2 deficient mice display impaired export of mucins from the ER and no activation of UPR [61][62][63]. These studies support the role of Agr2 in reducing ER stress during the production of large amounts of mucins.…”
Section: Journal Of Clinical and Cellular Immunologysupporting
confidence: 63%
“…These studies support the role of Agr2 in reducing ER stress during the production of large amounts of mucins. Consistent with its role in mucus processing the expression of Agr2 in airway epithelial cells is regulated via the IL-13-dependent STAT-6 pathway and Spdef [61,63]. Recently, Foxp1 was identified as another transcriptional regulator of Agr2.…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 85%
See 1 more Smart Citation
“…AGR2 was discovered in Xenopus laevis and is associated with cement gland differentiation [32]. As a member of the protein disulfide isomerase family, AGR2 has a thioredoxin-like domain to aid protein folding and assembly [33,34] and its expression is elevated in the preneoplastic tissue in Barrett's oesophagus and other human cancer cells, where it functions as a proto-oncogene [35][36][37]. AGR2 interacts with multiple proteins including DNA binding proteins and AAA þ ATPase [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Mice with a mutation in the endoplasmic reticulum stress response key regulator XBP1 are more susceptible to induced colitis (28), but how this affects Muc2 has not been studied. The Agr2 protein, which has a special thioredoxin-like domain, is essential for the in vivo production of Muc2, and Agr2-null mice are highly susceptible to colitis (29,30). Finally, it has also been observed that several mouse strains with mutations causing a dysfunctional Muc2 mucin show a strong unfolded response (31).…”
Section: Structure Of Muc2 Mucinmentioning
confidence: 99%